2013
DOI: 10.1111/bcp.12114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extremes of body weight on the pharmacokinetics, pharmacodynamics, safety and tolerability of apixaban in healthy subjects

Abstract: AIMApixaban is an oral, direct, factor-Xa inhibitor approved for thromboprophylaxis in patients who have undergone elective hip or knee replacement surgery and for prevention of stroke and systemic embolism in patients with non-valvular atrial fibrillation. This open label, parallel group study investigated effects of extremes of body weight on apixaban pharmacokinetics, pharmacodynamics, safety and tolerability. METHODFifty-four healthy subjects were enrolled [18 each into low (Յ50 kg), reference (65-85 kg) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
208
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(223 citation statements)
references
References 37 publications
11
208
1
3
Order By: Relevance
“…The model allowed for empirical separation of the total plasma CL/F into renal and nonrenal components with predicted increases in AUC ss of 9%, 28%, and 55% for patients with NVAF with mild (cCrCL = 65 mL/minute), moderate (40 mL/minute), and severe (15 mL/minute) renal impairment, respectively, compared with those with normal renal function. The results are generally consistent with the estimates from phase I studies20, 22 in which mild, moderate, and severe renal impairment were associated with an ~16%, 29%, and 44% higher estimated apixaban AUC INF than those with normal renal funtion 20. Several factors identified in previous phase I clinical trials, including age, sex, body weight, and mild‐to‐moderate renal impairment, were shown to modestly influence apixaban PK and these factors alone do not require any clinical dose adjustment.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The model allowed for empirical separation of the total plasma CL/F into renal and nonrenal components with predicted increases in AUC ss of 9%, 28%, and 55% for patients with NVAF with mild (cCrCL = 65 mL/minute), moderate (40 mL/minute), and severe (15 mL/minute) renal impairment, respectively, compared with those with normal renal function. The results are generally consistent with the estimates from phase I studies20, 22 in which mild, moderate, and severe renal impairment were associated with an ~16%, 29%, and 44% higher estimated apixaban AUC INF than those with normal renal funtion 20. Several factors identified in previous phase I clinical trials, including age, sex, body weight, and mild‐to‐moderate renal impairment, were shown to modestly influence apixaban PK and these factors alone do not require any clinical dose adjustment.…”
Section: Discussionsupporting
confidence: 84%
“…Individually, these factors have been shown to have limited effects on exposure,20, 21, 22 both within the analyses described herein as well as in individual trials. In addition, each of these factors on their own was not expected to result in clinically meaningful change in the benefit–risk profile of apixaban, as confirmed by a subgroup analysis performed in subjects who met only one of the dose‐reduction criteria 37.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A subgroup analysis of the ARISTOTLE trial based on BW reported that higher BW and BMI were associated with lower all‐cause mortality rate and lower risk of stroke or systemic embolism 22. A pharmacokinetic study of healthy volunteers taking rivaroxaban reported that the area under the curve (AUC) was unaffected by BW,23 the volume of distribution was moderately influenced by BW in patients taking rivaroxaban,24 and a mean increase in BW of 83% resulted in a limited 23% decrease of the AUC in healthy volunteers taking apixaban 25. A large prospective study of real‐life patients receiving DOACs for treatment of atrial fibrillation or VTE, which included 98 patients with BMI >40 kg/m 2 , did not find any indication that high BMI is associated with reduced DOAC efficacy or safety 26.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies of metabolism and/or pharmacokinetics briefly presents the LC-MS/MS methods applied to determine apixaban plasma lev- [25], and Wang et al [26] determined pharmacokinetics of apixaban in healthy subjects using a LC-MS/MS method validated by Intertek Pharmaceutical Services with a LLOQ of 1 ng/mL. Frost et al studied pharmacokinetics of apixaban after single dose in healthy subjects by a LC-MS/MS method with LLOQ of 1 ng/mL and quantification range of 1 -1000 ng/mL [7].…”
Section: Discussionmentioning
confidence: 99%